Data Analysis Techniques for Physical Scientists - A. Pruneau, Claude (Cambridge University Press, 2026)
A comprehensive guide to data analysis for the physical sciences including probability, statistics, data reconstruction, and Monte Carlo methods. This book provides a valuable resource for advanced students and seasoned researchers in experimental particle physics, nuclear physics and astrophysics. This title is available as open access on Cambridge Core.